Maintenance Electroconvulsive Therapy Augmentation on Clozapine-Resistant Psychosis with Neurosyphilis - Othman, Zahiruddin; Nordin, Muhammad Farhan (Japan International Cultural Exchange Foundation, 2018)
Introduction: Patients with neurosyphilis may present with severe neuropsychiatric sequelae which do not respond adequately even to clozapine which is regarded as the most efficacious medication for the treatment of schizophrenia. Clozapine augmentation with electroconvulsive therapy (ECT) has been shown to be an effective and safe treatment strategy for treatment-resistant schizophrenia. Objective: This case report aimed to describe a patient with neurosyphilis, whose psychotic symptoms did not improve significantly although he had multiple adequate medication trials including daily doses of fluoxetine 40 mg, olanzapine 15 mg, haloperidol 15 mg, sulpiride 1,000 mg, quetiapine 800 mg, and finally clozapine 150 mg. Result: The patient was stabilized with a combination of clozapine and maintenance ECT. A total of no less than 120 sessions of ECT (stimulus dose ranged 15-200% and seizure duration 8-57 seconds) were given by August 2017 while the clozapine was maintained at 75 mg bd. The patient had one episode of spontaneous seizure during induction of general anesthesia with etomidate. Otherwise, there was no documented serious adverse effect. Conclusion: Maintenance electroconvulsive therapy augmentation on clozapine-resistant psychosis with neurosyphilis is effective and safe but has never been reported in the literature to the authors' knowledge. It is hoped that this case report would contribute to the scarce literature on this augmentation strategy.